1989
DOI: 10.1128/jvi.63.6.2790-2797.1989
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral antibodies stimulate production of reactive oxygen species in cultured canine brain cells infected with canine distemper virus

Abstract: Canine distemper is characterized mainly by respiratory, enteric, and nervous symptoms. Infection of the central nervous system results in demyelination, to which inflammation has been shown to contribute significantly. It has been proposed that macrophages play a major role as effector cells in this process. We report that cultured dog brain cells contain a population of macrophages capable of producing reactive oxygen species as measured by luminol-dependent chemiluminescence. In cultures infected with canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 44 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…CDV has been reported as being able to trigger an increase in ROS intracellular levels, with the subsequent induction of oxidative stress in different kinds of cells such as microglia, in vitro as well as in vivo [31][32][33][34][35]. Similarly, the present study revealed increased ROS levels in DH82Ond pi cells, as demonstrated by an increased oxidative burst, as well as suggested by increased gene transcription of TXNIP and NCF4.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…CDV has been reported as being able to trigger an increase in ROS intracellular levels, with the subsequent induction of oxidative stress in different kinds of cells such as microglia, in vitro as well as in vivo [31][32][33][34][35]. Similarly, the present study revealed increased ROS levels in DH82Ond pi cells, as demonstrated by an increased oxidative burst, as well as suggested by increased gene transcription of TXNIP and NCF4.…”
Section: Discussionsupporting
confidence: 75%
“…ROS are highly chemically reactive molecules that can induce damage to cellular macromolecules such as nucleic acid and lipids, when they outnumber scavenging systems [28][29][30]. CDV infection can increase ROS production and ROS-induced damage in vitro and in vivo as shown for spontaneous CDV infection in dogs [31][32][33][34][35]. Furthermore, CDV can induce an accumulation of viral glycoproteins in the endoplasmic reticulum (ER) of Vero cells and primary rat neurons, resulting in increased endoplasmic reticulum stress [36], which has been reported as associated with an increased ROS production [37].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, demyelinated plaques of distemper are non-inflammatory (Higgins et al, 1982a,b;Summers et al, 1984aSummers et al, , 1995 but later it may acquire an inflammatory component (Summers et al, 1984a(Summers et al, , 1995. The inflammatory phenomenon is related to virus elimination from CNS (Vandevelde et al, 1985;Bollo et al, 1986) and can increase lesion severity possibly due to action of factors liberated by macrophages (Bu¨rge et al, 1989) and cellular cytotoxity against virus-infected cells (Bollo et al, 1986). Alldinger et al (1993) reported that in the demyelinating encephalitis of canine distemper, inflammation might be associated to restriction of surface viral protein expression, which contributes to virus persistence.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of bystander demyelination was investigated in CDV infected DBCC, which also contain numerous macrophages (Bi.irge et al, 1989). We used a chemoluminescence technique detecting the production of reactive oxygen radicals by stimulated macrophages (Btirge et al, 1989;Griot et al, 1989b;Griot et al, 1989a). We found that sera and CSF of dogs with inflammatory distemper were capable of stimulating macrophages in infected but not in uninfected cultures.…”
Section: Bystander Demyelination Associated With the Antiviral Immunementioning
confidence: 97%